Strategi Media Relations Partai Gelora Dalam Membangun Kepercayaan Publik - Zea Azzahira Alkayyisa Bahri; Tria Patrianti (Jurnal Mahasiswa Kreatif, 2024)
The aim of this research was to determine whether a political party can build public trust. This research examines the media relations carried out by the Gelora Party in building public trust. The background to this research is that political parties are state institutions that have the lowest percentage of trust among other state institutions, due to the lack of fulfillment of promises made. Therefore, the Gelora Party carries out various publicity in the media, one of which is through media relations, with the aim of providing information that will be published by the media and its crew, and with various information, one of which is providing education regarding political parties to the public, so that with this effort it is hoped that change the public's view of political parties. This research uses theories that are relevant to the matter under study, namely media relations strategy theory (Iriantara, 2019:94-110), as well as public trust theory (Haning, Hasniati & Tahili, 2020:25-39). The method used in this research is descriptive qualitative, the data collection technique used is primary data in the form of interviews with informants and secondary data in the form of documentation, both data and images. With the results of media relations research carried out by the Gelora Party in building public trust. Through the answers obtained from informants, it was stated that the media relations carried out could provide literacy about political parties to the public, build trust in the media and journalists and produce the highest percentage of popularity for newly established parties. It can be concluded that the media relations carried out by the Gelora Party have an impact on building public trust. This is also supported by Triangulation answers from senior journalists who assess the media relations carried out by the Gelora Party.